1983
DOI: 10.1021/jo00168a009
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective reductions of substituted cyclohexyl and cyclopentyl carbon-nitrogen .pi. systems with hydride reagents

Abstract: The internal cyclopropanation of several diversely substituted dienic diazo esters is described. Thermolysis of the resulting vinylcyclopropanes yielded cyclopentene-annulated lactones in good yields. Depending on the choice of the dienyl unit, either guaiane or pseudoguaiane substitution patterns of the cyclopentene portion were obtained. Stereochemical assignments based on 13C NMR data are provided for all of these lactones. Subsequent transformations of the bicyclic lactones to differentially functionalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0
3

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(60 citation statements)
references
References 0 publications
5
52
0
3
Order By: Relevance
“…The assignment of the relative stereochemistry at the bridging carbon C-7 in 14 and 15 was made in the following manner. The mixture of 14 and 15 was reduced with sodium borohydride in acetic acid (12) to afford a single product whose 360-MHz 'H nmr, elemental analysis, and mass spectral properties were correct for the gross structure of 16. Nuclear Overhauser enhancement (nOe) experiments, wherein saturation of the C-6 methyl resonance at 6 0.62 gave an enhancement in the signals for N-H, N-6 and H-7, while saturation of the methyl resonance at C-7 produced an enhancement of the signals for H-4 and H-7, unequivocally indicated that the product had the relative stereochemistry shown in 16.…”
Section: Resultsmentioning
confidence: 99%
“…The assignment of the relative stereochemistry at the bridging carbon C-7 in 14 and 15 was made in the following manner. The mixture of 14 and 15 was reduced with sodium borohydride in acetic acid (12) to afford a single product whose 360-MHz 'H nmr, elemental analysis, and mass spectral properties were correct for the gross structure of 16. Nuclear Overhauser enhancement (nOe) experiments, wherein saturation of the C-6 methyl resonance at 6 0.62 gave an enhancement in the signals for N-H, N-6 and H-7, while saturation of the methyl resonance at C-7 produced an enhancement of the signals for H-4 and H-7, unequivocally indicated that the product had the relative stereochemistry shown in 16.…”
Section: Resultsmentioning
confidence: 99%
“…Clean reduction of the enamine 10a was achieved using sodium triacetoxyborohydride, [28] performed from NaBH 4 in acetic acid (Scheme 4). The distilled amine 13 underwent crystallization as the perchlorate salt to provide a diastereomerically pure product as shown by 1 H and 13 C NMR data.…”
Section: Resultsmentioning
confidence: 99%
“…Nos últimos 30 anos, têm sido muito estudados e relatados na literatura métodos de redução estereocontrolada de cetonas cíclicas e cetonas cíclicas α,β-insaturadas. Hidretos pouco volumosos como NaBH 4 , LiAlH 4 e derivados foram avaliados exaustivamente, [11][12][13][14][15][16] bem como metais alcalinos em solução. 17 Resultados experimentais envolvendo cicloexanonas e cicloexenonas substituídas como substratos demonstraram que a direção preferencial do ataque ao anel (axial ou equatorial) possui forte dependência tanto do volume do hidreto atacante quanto do volume dos substituintes ao redor da carbonila.…”
Section: Introductionunclassified
“…Hidretos pouco volumosos, como NaBH 4 e LiAlH 4 , preferem quase exclusivamente ataques axiais, gerando álcoois pseudoequatoriais com diastereosseletividades variando de 72 a >96%. [12][13][14][15][16] Os modelos estereoquímicos mais aceitos para explicar esta preferência por um ataque axial são baseados em conceitos como o controle pela estabilidade do produto, e em uma abordagem estérica, pelos efeitos dos hidrogênios α-carbonila axiais, que podem repelir e/ou desenvolver efeito torsional quando de ataques equatoriais, e pelos efeitos estéricos dos hidrogênios β-carbonila axiais (Figura 1). Estudos computacionais [18][19][20][21][22][23][24][25] confirmaram que tanto efeitos eletrônicos quanto torsionais estão estreitamente relacionados à seleção facial na redução do sistema cicloexanona.…”
Section: Introductionunclassified
See 1 more Smart Citation